The Influence of Material and Roughness on the Settlement and the Adhesive Strength of the Barnacle Balanus Improvisus in the Baltic Sea - Petersen, Dennis S.; Gorb, Stanislav N.; Heepe, Lars (Frontiers in Marine Science, 2020)
Under natural conditions, barnacles, one of the most prominent marine hardfouling organisms, encounter a vast variety of heterogeneous surfaces including artificial ones, such as ship hulls on which they adhere efficiently. Despite intensive research in the last decades, it is still not clear, how material related factors influence the fouling development under natural conditions, and whether roughness at a microscale affects the release dynamics of barnacles. In order to shed light on the relationship between these substrate factors and their effect on biofouling, both settlement and fouling development of Balanus (=Amphibalanus) improvisus was evaluated on epoxy resin and polyvinylsiloxane (PVS) substrates differing in their roughness (flat, asperity sizes: 0.3µm, 1µm, 3µm, 9µm, 12µm) in a static field trial in the Baltic Sea for 17 weeks performed in 2014. All barnacles on these tested surfaces were individually tracked on a weekly basis, in order to calculate the release to settlement ratios (r/s), to evaluate the fouling- release performance and to monitor the actual attachment duration. It was demonstrated that both stiffness and surface free energy had no strong effect on initial settlement. The total fouling accumulation was nearly identical for epoxy resin and PVS, if fallen-off barnacles were included in the analysis. Roughness influenced initial settlement and fouling development. On PVS the r/s nged between 0.5-0.7 and the attachment duration was around four weeks. However, samples with a roughness of 9µm displayed a lower r/s ratio (0.35) and barnacles showed longer attachment durations (8 weeks). In a second field trial performed in 2017, attachment forces of barnacles were measured after the samples had been immersed for 10 weeks in the Baltic Sea. The shear stresses obtained were similar for substrates with different roughness with around 0.12 MPa and were independent of the barnacle’s size. These findings show that roughness even at the micro scale can impact the fouling release ability of a surface.